Innovative participatory crop improvement approaches for enhanced farm productivity, climate resilience, and efficient local seed systems - Mengistu, Dejene Kassahun; Terefe, Hailu; Hailemariam, Bogale Nigir; Tilahun, Mulugeta; Kidane, Yosef Gebrehawaryat; Fadda, Carlo (Bioversity International and International Center for Tropical Agriculture, 2025)
This report outlines the findings of participatory research aimed at enhancing agricultural resilience, productivity, and sustainability in the North Shewa (Amhara Region), East Shewa (Oromia Region), and Hadiya (Central Ethiopia) zones, areas increasingly vulnerable to climate change-related stresses. The initiative advanced low-input, high-resilience farming practices tailored to smallholder realities by prioritizing genetic and crop diversity, particularly durum wheat and faba bean. A cornerstone of the study was the deployment of crowdsourcing trials using the TRICOT (triadic comparison of technologies) method, engaging farmers as citizen scientists to evaluate pre-selected varieties under real farmers’ management conditions. The research successfully up-scaled durum wheat “winner” varieties such as Melfa, Geregera, Meket-1, and Wehabit, and faba bean varieties such as Numan, Tumsa and Gora to 1,140 farmers (221 of them women) planted on 150+ hectares of land during the 2023–2024 cropping season; and the crops are still under production in this reporting time too. A total of 38,929 kg of seed was distributed to complement the farmer-to-farmer seed exchange and cooperative-based seed multiplication, ensuring continuity beyond project boundaries. Reported yields reached up to 7 t ha-1 for durum wheat and 2.8 t ha-1 for faba bean, with farmers highlighting benefits like rust and fab bean gall resistance for durum wheat and faba bean, respectively, reduced agrochemical use, and superior culinary quality (e.g., soft injera from Melfa). Farmers were trained on the benefits of optimizing agronomic practices, varietal diversification, and maintaining local seed systems. Capacity building training was provided to a total of 827 farmers, of which 170 (20.56%) are women and 63 experts (33.33% women) who directly facilitate agriculture in the project intervention areas. As a result, the initiative appreciably transformed smallholder seed portfolios and seed systems. The informal seed system was revitalized through community seed multiplication, cooperatives, and gender-inclusive decision-making, with women actively participating in varietal evaluation and ranking, leading to more equitable adoption and household nutrition outcomes. In summary, this participatory research initiative highlighted that climate resilience, productivity, and equity in smallholder farming can be advanced through an integrated strategy: diversifying genetic resources, empowering farmers as co-researchers, tailoring agronomy to local varieties and conditions, and strengthening decentralized seed systems. By centering farmer knowledge, gender inclusion, and ecological sustainability, the results of the studies offer a scalable and resilient pathway for Ethiopian agriculture in an era of accelerating climate uncertainty.